Organocatalytic Oxidation of Secondary Alcohols Using 1, 2‐Di(1‐naphthyl)‐1, 2‐ethanediamine (NEDA). Issue 28 (27th August 2014) - Al‐Hunaiti, Afnan; Räisänen, Minna; Pihko, Petri; Leskelä, Markku; Repo, Timo
Abstract: Diamine, 1, 2‐di(1‐naphthyl)‐1, 2‐ethanediamine (NEDA), efficiently catalyzes the oxidation of alcohols by using TBHP as an oxidant. Notably, secondary benzyl alcohols are oxidized in almost quantitative yields, and the catalyst also displays high activity towards even hindered cycloaliphatic secondary alcohols. With enantiopure ( R, R )‐NEDA, oxidative kinetic resolution can be realized and depending on the alcohol ee up to 99 % are achieved. Abstract : A nonmetal catalytic oxidation of alcohols with preferential oxidation of secondary alcohols by diamine is developed. 1, 2‐Di(1‐naphthyl)‐1, 2‐ethanediamine (NEDA) is used as catalyst to selectively oxidize secondary alcohols in the presence of TBHP as terminal oxidant. The chiral NEDA is also studied and shows promising enantioselectivity in oxidative kinetic resolution of racemic secondary alcohols with good to excellent ee values.